Identifikasi Pengetahuan dan Keterampilan Tukang Besi Beton Berdasarkan SKKNI Pada Proyek Konstruksi di Kota Ambon - F Hamid; F A Sangadji; I Oppier; S I Latuconsina (Cered Indonesia Institute, 2023)
Standar Kompetensi Kerja Nasional Indonesia (SKKNI) are standards for the qualifications and skills of construction workers regulated by the government through the Ministry of Public Works. Workers who meet SKKNI standards are workers who have certified skills and knowledge and are of higher quality than craftsmen who have not been certified. In the city of Ambon, it is still questionable whether each part of the competency in the SKKNI is needed enough in the city of Ambon considering that most of the craftsmen we find still have minimal education and not all of the SKKNI standards can be mastered by the craftsmen. Based on this background, the aim of this research is to determine the percentage of competency elements in the knowledge and skills of concrete iron workers based on SKKNI on construction projects in the city of Ambon. The method used in this research is a survey method. The data collection technique used was by distributing questionnaires. After the questionnaire data has been collected, the data is then tested for validity and reliability using the SPSS program. Next, the questionnaire data was analyzed descriptively to determine the percentage of knowledge and skills. From the tabulation of data and research results, it was found that the variable with the highest percentage score in the knowledge section was at